Coronary CT angiography: State of the art - Sun, Zhonghua; Sabarudin, Akmal (Beijing Baishideng BioMed Scientific Co., Ltd, 2013)
Coronary computed tomography (CT) angiography has been recognized as the most rapidly developed imaging technique in the diagnosis of coronary artery disease due to the emergence and technological advances in multislice CT scanners. Coronary CT angiography has been confirmed to demonstrate high diagnostic and predictive value in coronary artery disease when compared to invasive coronary angiography. However, it suffers from high radiation dose which raises concerns in the medical field. Various dose-reduction strategies have been proposed with effective outcomes having been achieved to reduce radiation exposure to patients. This article provides an introduction and overview of the series of articles that will focus on each particular topic related to coronary CT angiography.